Research on Resource Recovery Technology for Aluminum Alloy Anodizing Liquor Based on Clean Production - ZHENG Haoqing, WEI Zhe, WEI Lian (Cailiao Baohu)
In order to prolong the service life of aluminum alloy anodizing liquor and reduce pollution， aluminum was recovered from the anodizing liquor using ion exchange resin.Based on single factor experiments， response surface optimization experiments were conducted to optimize the resin adsorption and regeneration processes， while the experimental design and model analysis were performed using Design-Expert 8.0.6.As a result，the optimal conditions for resin adsorption of aluminum ions were obtained:the reaction time was 10 min，the resin dosage was 360 g/L， and the aluminum ion exchange rate was 68.35%.The optimal conditions for resin regeneration were also obtained: the concentration of the regenerated solution was 4.15%， the dosage of the regenerated solution was 8.57 mL/g， and the regeneration time was 30 min， achieving a resin regeneration rate of 91.07%.After multiple cycles of resin use， the aluminum ion exchange rate and resin regeneration rate were maintained at around 53%and 84%， respectively.